2020
DOI: 10.3390/ijms21165621
|View full text |Cite
|
Sign up to set email alerts
|

A Foundational Study for Normal F8-Containing Mouse Models for the miRNA Regulation of Hemophilia A: Identification and Analysis of Mouse miRNAs that Downregulate the Murine F8 Gene

Abstract: Hemophilia A (HA) is associated with defects in the F8 gene, encoding coagulation factor VIII (FVIII). Our previous studies show that F8-targeting micro RNAs (miRNAs), a group of small RNAs involved in gene regulation, can downregulate F8 expression causing HA in individuals with normal F8-genotypes and increased HA severity in patients with mutations in F8. Understanding the mechanistic underpinnings of human genetic diseases caused or modulated by miRNAs require a small animal model, such as a mouse model. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…12 They also found that murine miRNAs, including miR-208a, miR-351 and miR-125a, could target the 3'UTR of F8 mRNA in mouse models and mammalian cells. 13 The above evidence strongly supports the involvement of miRNAs in the pathogenesis of HA.…”
supporting
confidence: 61%
“…12 They also found that murine miRNAs, including miR-208a, miR-351 and miR-125a, could target the 3'UTR of F8 mRNA in mouse models and mammalian cells. 13 The above evidence strongly supports the involvement of miRNAs in the pathogenesis of HA.…”
supporting
confidence: 61%
“…As presented in Figure 3, both miRNAs had higher expression in the acquired haemophilia samples compared to healthy and mild haemophilia, while in the comparison with other groups the expression was less intense. Moreover, the interaction of miRNAs and 3'UTR of F8 gene was evaluated in murine models, the study conducted by Jankowska reported miR‐208a, miR‐351 and miR‐125a as modulators of F8 gene by their interaction with 3'UTR of F8 gene, 27 furthermore similar study reported 52 miRNAs that interact with F7 , F8 and other haemostatic‐associated genes 28 …”
Section: Discussionmentioning
confidence: 99%